Vacinação na primeira infância no contexto da pandemia da Covid-19: construção e validação de um guia de consulta rápida - Lucas, Simone Oliveira (2021)
The pandemic of COVID-19 has put health professionals in a process of knowledge construction and accelerated update, requiring that the assistance be practiced assertively, in order to keep the patient safe. The use of tools to standardize the care provided can be pointed as an object of improvement in the quality of services. Thus, this study aimed to produce and validate a quick reference guide for the technical orientation of the work process related to vaccination in early childhood, in the pandemic context caused by the new coronavirus. Specifically, it sought to develop it in a regionalized way, geared to the reality of small municipalities, offering vaccinators a mechanism to improve professional practice, guiding them about the logistics and routine of vaccination, considering the rules of social distance, paramentation and interaction between vaccines, in addition to identifying the facilities, difficulties and potentialities to reorient the work processes. The theoretical referential appropriated the theoretical discussion of the themes from researches of renowned authors in the specific area of health, to the ergological approach, which underlies the work process. The methodology used was a cross-sectional, quali-quantitative research. The study took place from July to November 2021. Data collection to support the development of the guide occurred in the municipality of Miraíma, through an interview with nurses from the five registered Family Health Units, seeking to identify the possibilities and impasses in vaccination during the pandemic. The answers were evaluated using the SWOT/FOFA matrix, supporting the construction of the tool. Then, the guide was validated by judges with proven experience in Primary Health Care (PHC) and/or child health, using the Delphi technique, which is a systematized method of judging information, aimed at reaching a consensus of opinions on a particular subject, from the knowledge of a group of experts, through a questionnaire. The judgment of the variables was calculated using the Content Validity Index (CVI), which should be higher than 0.78. Compliance with the bioethical principles of autonomy, risks and benefits, non-maleficence, and protection of the research subject was taken into consideration. The purpose of the study to construct and validate the quick reference guide was achieved, since its CVI was equal to 1, reaching agreement on all individual points and on the content in general. This is the first instrument produced specifically in this perspective, registered in the seven municipalities of the 6th Health Decentralized Area of Itapipoca. Its use in PHC will provide theoretical basis for nursing care with vaccines and provide the improvement of professionals' interventions.